Analysis of the Needs for Developing E-Modules for Microbiology Practicum in the Biology Education Program at Raden Fatah State Islamic University Palembang - Ranti, Ranti; Wardhani, Sri; Habisukan, Ummi Hiras (Bioilmi: Jurnal Pendidikan, 2024)
Needs analysis is a systematic process for determining objectives, identifying actual and expected conditions, and prioritizing actions. Needs analysis in the development procedure is carried out to determine the students' assessment of the practicum guide used and the expectations of the practicum guide to be made.The purpose of this study was to analyze student needs for the development of e-modules for microbiology practicum in the biology education study program at UIN Raden Fatah Palembang. This type of research is descriptive qualitative, while the instruments used are student questionnaires and interview guidelines for lecturers and laboratory assistants. The results obtained are 55% of students like microbiology courses, 78% of students like practicum methods, low student science process skills, learning microbiology has been with practicum activities, there is already a practicum guide but it is still printed and not model-based, 46% of students like practicum guides with laboratory assistant direction, 57% of difficult material is sensitivity to antimicrobial substances. In conclusion, it is necessary to develop a practicum guidebook based on the guided inquiry model and integrated with technology on the material of sensitivity to antimicrobial substances to improve the science process skills of biology education students at UIN Raden Fatah Palembang.